2017
DOI: 10.1016/j.medengphy.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic parameters that may predict false-lumen growth in type-B aortic dissection after endovascular repair: A preliminary study on long-term multiple follow-ups

Abstract: Thoracic endovascular aortic repair (TEVAR) is commonly applied in type-B aortic dissection. For patients with dissection affects descending aorta and extends downward to involve abdominal aorta and possibly iliac arteries, false lumen (FL) expansion might occur post-TEVAR. Predictions of dissection development may assist in medical decision on re-intervention or surgery. In this study, two patients are selected with similar morphological features at initial presentation but with different long-term FL develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 35 publications
3
50
0
Order By: Relevance
“…The correct assessment of WSSbased indices in these regions of the FL can have important prognostic value. For example, as recently reported by Xu et al [28], the short-term variation of the Relative Residence Time (RRT), which is based on TAWSS and OSI (RRT = [(1-2⋅OSI)⋅TAWSS] -1 ), might be related to the post-TEVAR long-term FL remodelling.…”
Section: Aortic Dissection Case Studymentioning
confidence: 79%
See 1 more Smart Citation
“…The correct assessment of WSSbased indices in these regions of the FL can have important prognostic value. For example, as recently reported by Xu et al [28], the short-term variation of the Relative Residence Time (RRT), which is based on TAWSS and OSI (RRT = [(1-2⋅OSI)⋅TAWSS] -1 ), might be related to the post-TEVAR long-term FL remodelling.…”
Section: Aortic Dissection Case Studymentioning
confidence: 79%
“…Pressure differences between TL and FL might provide important diagnostic and prognostic information [28], but cannot be easily assessed in the clinic. For instance, higher pressure in the FL can lead to further expansion, or even rupture of the FL, whilst causing a narrowing of the TL [5,7].…”
Section: Aortic Dissection Case Studymentioning
confidence: 99%
“…As shown by Rudenick et al [10] via a lumped parameter model and confirmed by Bonfanti et al [11] with a CFD model, the wall compliance can indeed have a significant effect on the pressure in the FL, in particular when the size of the connecting tears is small. However, the majority of published AD models [12][13][14][15][16][17] assumes rigid-walls and neglects compliance effects on the predicted pressures. Advanced CFD models of AD account for the motion of the vessel walls using fluidstructure interaction (FSI) or moving boundary approaches [11,[18][19][20] which, in order to be patient-specific, need to be informed by nonroutine displacement data obtained, for example, via cine-MRI.…”
Section: Introductionmentioning
confidence: 99%
“…The same pulsatile velocity and pressure boundary conditions were assigned for each patient case (CTA-reconstructed model and VSA-simulated model) at the inlet and outlets. The inlet velocity boundary at the ascending aorta and the outlet velocity at the three aortic branches for each patient were obtained by ultrasound velocimetry as described in our previous study 30 , and the outlet pressure boundaries at the abdominal branches and common iliac arteries for each patient were assigned according to 31 . The vessel walls of both the CTA-reconstructed and VSA-simulated models were assumed to be rigid.…”
Section: Methodsmentioning
confidence: 99%